Remodeling of the microbiota improves the environmental adaptability and disease resistance in Tibetan pigs - Chang, Zhenyu; Bo, Suxue; Xiao, Qingqing; Wang, Yu; Wu, Xi; He, Yuxuan; Iqbal, Mujahid; Ye, Yourong; Shang, Peng (Frontiers in Microbiology, 2022)
Introduction The establishment of intestinal microbiota and the maintenance of its equilibrium structure plays an important role in Tibetan pigs during different growth stages. Understanding the structure and function of the intestinal microbiota at different growth stages of Tibetan pigs can provide a theoretical basis for guiding nutritional regulation and feeding management in different stages. Methods Fecal samples were collected from the Tibetan piglets at different growth stages, and the 16S rRNA was sequenced to analyze the changes of intestinal microbiota. Results Alpha and Beta diversity indexes showed that the diversity of the intestinal microbiota did not change during the three growth stages, and the main components of intestinal microbiota were not significantly different. At the phylum level, Firmicutes and Bacteroidetes were dominant and abundant at different growth stages and were not restricted by age. At the genus level, Streptococcus, Lactobacillus, and Bifidobacterium were the most dominant in the TP10d and TP40d groups, Streptococcus was the most dominant in the TP100d group, followed by Treponema_2 and Lactobacillus. Fusobacteria, Gluconobacter, and Synergistetes were found to be specific genera of 10-day-old Tibetan piglets by LEfSe combined with LDA score. The change of diet made Tenericutes and Epsilonbacteraeota, which are closely related to digestive fiber, become specific bacteria at the age of 40 days. With the consumption of oxygen in the intestine, obligate anaerobes, such as Verrucomicrobia, Fibrobacter, and Planctomycetes, were the characteristic genera of 100 days. KEGG function prediction analysis showed that the intestinal microbiota function of Tibetan pigs changed dynamically with the growth and development of Tibetan piglets. Discussion In conclusion, the structure and composition of the intestinal microbiota of Tibetan pigs are significantly different at different growth and development stages, which plays an important role in their immune performance.